Intra-abdominal fish bone Foreign body Abscess: Imaging Experience in a Tertiary Hospital (Bangladesh Journal of Radiology and Imaging, 2026)
The accidental ingestion of foreign body fish bones may sometimes cause penetration injuries. Peritoneal migration may occur with the fish bone to lie in the same or a different compartment or organ leading to complicating abscess formation. Patient usually present with the complains of nonspecific abdominal pain. Plain radiograph has low sensitivity. Computed tomography (CT) is the choice of investigation for definite diagnosis. Ultrasound is a widely used modality but not popular in the emergency setting of undifferentiated or GI abdominal pain. We present herein five patients referred with abdominal pain and tried to validate our experience for the use of ultrasound as an alternative diagnostic tool in most of cases of fish bone foreign body abscess.BJRI, 2024; VOL. 32(2): 153-157